OPTIMALISASI PENGAJIAN RUTIN MASJID AL-AQOBAH 7 PALEMBANG SEBAGAI UPAYA PEMBERDAYAAN MASYARAKAT - Anang Walian (Yonetim Jurnal, 2021)
This research is entitled Optimizing the Routine Recitation of Masjid Al-Aqobah 7 Palembang as Community Empowerment Effort in the Field of Islamic Insights. This study aims to determine: the background of holding routine recitation, optimization of routine recitation, constraints of routine recitation, opportunities to advance routine recitation, and implementation of routine recitation management at Masjid Al-Aqobah 7 Palembang. This research is a field research with data used in the form of qualitative data. The data collection techniques in this study were through interviews, observation, and documentation. Meanwhile, the data analysis technique uses three kinds of analysis stages: data reduction, data display, verification and conclusion drawing. This analysis is commonly called the Interactive Model Analysis based on Miles and Huberman's theory. The results of the study found that the background of holding routine recitation at Masjid Al-Aqobah 7 Palembang is: lack of Islamic knowledge in the mosque administrators and the surrounding community, as an effort to manage mosque management, the mosque as a place of Islamic civilization. Efforts to optimize the routine recitation of Masjid Al-Aqobah 7 Palembang can be done by: utilizing existing facilities, using thin books, a combination of study methods, consumption, attendance lists, congregational social media groups, inviting well-known preachers, inviting the public direct, and gradual delivery of material. Some of the obstacles to the routine recitation of the Al-Aqobah 7 Palembang mosque are: short time, lack of public interest in learning, financial problems, busy management, technical constraints, and differences in schools. Then there are several opportunities to advance the routine recitation of the Al-Aqobah 7 Palembang mosque: domicile of the mosque on the side of the main road, the number of housing around the mosque, the strong commitment of the speakers, the strong commitment of the board, optimization of youth and mothers. Meanwhile, the implementation of routine recitation management at Masjid Al-Aqobah 7 Palembang through four management functions: planning, organizing, implementing, and evaluating. Keywords: Optimization, Routine Studies, Community Empowerment.